2018
DOI: 10.1302/1863-2548.12.170056
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric tibial shaft fractures treated by open reduction and stabilization with monolateral external fixation

Abstract: PurposeElastic stable intramedullary nailing is increasingly used for surgical treatment of tibial shaft fractures, but frequently requires immobilization and delayed full weight-bearing. Therefore, external fixation remains interesting. The aim was to report clinico-radiological outcomes of monolateral external fixation for displaced and unstable tibial shaft fractures in children.MethodsAll tibial fractures consecutively treated by monolateral external fixation between 2008 and 2013 were followed. Inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…No premature frame removal, Limb length discrepancy, osteomyelitis, compartment syndrome, delayed union, neurovascular injury was seen in any case No case required bone grafting or corrective osteotomy. No refracture was seenin any case following fixator removal [6,11,17] however high energy fractures are associated with soft tissue injury so selection of treatment modality becomes difficult [1,11] Unlike adults there are no clear cut guide lines for management of open tibial fractures in skeletally immature patient [1,12,13] As per literature open fractures with more than 10 yrs of age are associated with outcomes and complications like adults as compared to children less than 10 yrs of age [1] . Remodelling potential decreases with age more than 10 years [1] which may lead to residual deformity, therefore aim of treatment should be fracture union with minimal deformity in children more than 10 years [1,11] Many treatment modalities are available from conservative to operative.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…No premature frame removal, Limb length discrepancy, osteomyelitis, compartment syndrome, delayed union, neurovascular injury was seen in any case No case required bone grafting or corrective osteotomy. No refracture was seenin any case following fixator removal [6,11,17] however high energy fractures are associated with soft tissue injury so selection of treatment modality becomes difficult [1,11] Unlike adults there are no clear cut guide lines for management of open tibial fractures in skeletally immature patient [1,12,13] As per literature open fractures with more than 10 yrs of age are associated with outcomes and complications like adults as compared to children less than 10 yrs of age [1] . Remodelling potential decreases with age more than 10 years [1] which may lead to residual deformity, therefore aim of treatment should be fracture union with minimal deformity in children more than 10 years [1,11] Many treatment modalities are available from conservative to operative.…”
Section: Resultsmentioning
confidence: 99%
“…Remodelling potential decreases with age more than 10 years [1] which may lead to residual deformity, therefore aim of treatment should be fracture union with minimal deformity in children more than 10 years [1,11] Many treatment modalities are available from conservative to operative. Operative treatment ranges from elastic nails, rigid nails, plates, monolataeral external fixator & ilizarov ring fixator, Taylors special frame, Supracutaneous platting [2,4,5,6,11,17] Tibia has relatively poor soft tissue envelop & variable blood supply which can be affected by initial trauma and further internal fixation may even reduce tissue viability leading to impairment in fracture healing [3,4] Risk of infection can be more in open fractures fixed internally [4,7] Elastic nails are minimally invasive and most favoured method by orthopaedic surgeons, but they are less stable in comminuted fractures [6,15] . Internal fixation by them also needs immobilization and support with splint for certain duration of time [15,16] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the excluded full texts, the most common reason for exclusion was that open fractures could not be separated (10 studies) [19][20][21][22][23][24][25][26][27][28] followed by studies with too small population (7 studies). [29][30][31][32][33][34][35] In two studies, 36,37 distal tibia fractures were no distinguishable from diaphyseal fractures, and two studies 38,39 reported only the incidence of compartment syndrome.…”
Section: Resultsmentioning
confidence: 99%